Measuring the impact of influenza vaccination national strategy among the at risk Portuguese population - Machado, Ausenda (2021)
Tese de doutoramento em Saúde Pública (especialidade em Epidemiologia) apresentada à Escola Nacional de Saúde Pública, Universidade NOVA de Lisboa, 2020